(untitled) (Research, Society and Development, 2021)
Fish farming is an economic activity that has been gaining ground and growing in recent years, becoming an alternative income that contributes to leveraging the generation of employment in rural areas. The municipality of Arari-MA stands out with regard to the fish activity that represents one of the potential activities in the region. However, it has been accompanied by problems that hinder the development of the activity. In this sense, the objective of the work was to identify the main challenges found in the commercialization of fish for the producers of the association of fish farmers of Arari “ASPAR”. The next phase corresponded to the interviews through questionnaires, in which 11 ASPAR producers participated in order to obtain information on the commercialization. It was found that the main obstacles in the commercialization process occur due to the high cost of inputs, obtaining documentation, labor, limitations in the search for commercialization channels, lack of technical assistance. The lack of documentation such as environmental licensing prevents obtaining credits from banks, compromising commercialization mainly with regard to the purchase of feed, and in the construction of structures for the direct sale of fish to the final consumer, reflecting on low profitability. It is recommended that ASPAR fish farmers seek a greater organization within the association to neutralize mainly the problem related to the purchase of feed, also requiring public and private institutions to take strategic actions to improve the marketing process, especially in relation to legalization and assistance. technique for fish farms.